Application of nonsense-mediated primer exclusion (NOPE) for preparation of unique molecular barcoded libraries - Shagin, Dmitriy A; Turchaninova, Maria A; Shagina, Irina A; Shugay, Mikhail; Zaretsky, Andrew R; Zueva, Olga I; Bolotin, Dmitriy A; Lukyanov, Sergey; Chudakov, Dmitriy M (BMC genomics, 2017)
BACKGROUND: Recently we proposed efficient method to exclude undesirable primers at any stage of amplification reaction, here termed NOPE (NOnsense-mediated Primer Exclusion). According to this method, added oligonucleotide overlapping with the 3'-end of unwanted amplification primer (NOPE oligo) simultaneously provides a template for its elongation. This elongation disrupts specificity of unwanted primer, preventing its further participation in PCR. The suggested approach allows to rationally manage the course of PCR reactions in order to facilitate analysis of complex DNA mixtures as well as to perform multistage PCR bypassing intermediate purification steps. RESULTS: Here we apply NOPE method to DNA library preparation for the high-throughput sequencing (HTS) with the PCR-based introduction of unique molecular identifiers (UMI). We show that NOPE oligo efficiently neutralizes UMI-containing oligonucleotides after introduction of UMI into sample DNA molecules, thus allowing to proceed with further amplification steps without purification and associated loss of starting material. At the same time, NOPE oligo does not affect the efficiency of target PCR amplification. CONCLUSION: We describe a simple, robust and cheap modification of UMI-labeled HTS libraries preparation procedure, that allows to bypass purification step and thus to preserve starting material which may be limited, e.g. circulating tumor DNA, circulating fetal DNA, or small amounts of isolated cells of interest. Furthermore, demonstrated simplicity and robustness of NOPE method should make it popular in various PCR protocols.
Keywords: Sequence Analysis, DNA; Unique molecular identifiers; Targeted resequencing; DNA primery; sekvenční analýza DNA; PCR; Gene Library; Polymerase Chain Reaction; polymerázová řetězová reakce; genová knihovna; DNA Primers; ErbB Receptors; erbB receptory; High-throughput sequencing; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing